TBzTD : a secondary accelerator for stable crosslink systems in tire applications - Ferrandino M P; Hong S W; Sanders J A (Rubber World, 1996)
Tetrabenzylthiuram disulfide (TBzTD)/sulfenamide systems (0.25 to 1.25phr) provide a powerful tool in applications requiring scorch safety, efficient cures and nitrosamine safety. The high MW of TBzTD and the amine used to fabricate the molecule give accelerator properties not possessed by lower MW thiurams. Truck tire tread, base tread and bead filler are good applications for this system.
Source Year: 1996
Keywords: Crosslink systems; TBzTD; Tire